Neural correlate of the contextual interference effect in motor learning: A kinematic analysis - Lin, C. H.; Fisher, B. E.; Wu, A. D.; Ko, Y. A.; Lee, L. Y.; Winstein, C. J. (Journal of Motor Behavior, 2009)
The contextual interference (CI) effect affirms that learning is enhanced when interference during practice is high, such as when participants practice multiple tasks in a random order. Previous research showed a distinct response in the cortical motor (CM) regions of participants performing under high CI practice conditions compared with low CI conditions. Specifically, there was increased corticomotor activity in a high CI condition when participants practiced 3 arm tasks, each with specific spatial and temporal requirements. Using disruptive transcranial magnetic stimulation (TMS), the authors' purpose was to determine whether CM is preferentially processing the spatial, temporal, or both parameters of the task during high CI practice. Participants were randomized to 1 of 6 practice conditions derived from 3 stimulation conditions (no TMS, TMS, sham TMS) and 2 CI conditions (blocked [low CI] and random [high CI]). The authors measured performance accuracy in movement timing (temporal) and amplitude (spatial) across practice and no-stimulation recall phases. TMS perturbation deterred learning of movement timing under random, but not blocked, practice order; the authors did not observe this in spatial parameter learning. The authors' data suggest that increased corticomotor activity during high CI practice may reflect preferential processing of the temporal parameter of the task.